Protective effects of caffeic acid phenethyl ester (CAPE) and thymoquinone against cigarette smoke in experimental bone fracture healing - Acikan, Izzet; Yaman, Ferhan; Dundar, Serkan; Ozercan, Ibrahim Hanifi; Atilgan, Serahim Serhat (Elsevier B.V., 2022)
This study investigated the protective characteristics of caffeic acid phenethyl ester (CAPE) and thymoquinone (TMQ) against the effects of cigarette smoke in recovery from bone fractures. Sixty Wistar albino rats were divided into six groups (n = 10). The rats’ femur bones were fractured and then fixed with microplates and microscrews. In the CAPE group, CAPE was given by intraperitoneal injection for 30 days at a dose of 10 ?mol/kg once a day. In the TMQ group, TMQ was given orogastrically for 30 days at a dose of 10 mg/kg once a day. In the cigarette groups, CAPE was given by intraperitoneal injection for 30 days at a dose of 10 ?mol/kg once a day (CAPE-CG), TMQ was given orogastrically for 30 days at a dose of 10 mg/kg once a day (TMQ-CG), and controls were exposed to cigarette smoke three times a day for 8 min each time for 30 days. The controls received no postoperative treatment. The rats were sacrificed on the 30th day following surgery. According to the histopathological and immunohistochemical results, cigarette smoke had a negative impact on bone healing. TMQ and CAPE increased bone formation and reduced bone destruction. Therefore, TMQ and CAPE were found to be partially protective against the adverse effects of smoking on bone tissue. © 2022
Keywords: Bone fracture healing; Caffeic acid phenethyl ester; Smoking; Thymoquinone